Prevention of bone metastases in breast cancer - L. M. Kogonia (ABV-press, 2014)
The paper deals with the prevention of bone metastases in patients with breast cancer (BC). The drugs from a group of bisphosphonates are ascertained to play an important role in combination therapy for bone metastases. Bonefos (clodronate) is one of these agents used in BC patients for prophylaxis.